ANALISIS PENGARUH FRUAD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN (Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018- 2019) - Amirotuz Zakkiyah; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to analyze and test the effect of the Fruad triangle (Pressure, Opportunity and Rationalization) on fraudulent financial statements in Food and Beverage companies listed on the Indonesia Stock Exchange in 2018-2019. The type used in this study is a quantitative method that can be used to examine the population.  and certain samples, as data collection using research instruments, data analysis is quantitative or statistical.  The population in this study were 30 manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2019. The sample was taken from the population using purposive sampling technique and obtained a sample of 20 companies with the criteria used. The results showed that simultaneously Pressure, Opportunity and Rationalization Affected Fraudulent Financial Statements partially Pressure had a positive and significant effect on financial statements while Opportunity and Rationalization had no significant effect on financial statement fraud in Food and Beverage companies listed on the IDX in 2018-2019  .Keywords: Financial statements, fraud triangle, pressure, opportunity and rationalization